Recent applications of heteropolyacids and related compounds in heterocycles synthesis - Romanelli, Gustavo Pablo (2009)
Heteropolyacids (HPAs) and related compounds have received considerable attention as solid acids in recent years. HPAs possess unique physicochemical properties, with their structural mobility and multifunctionality being the most important for catalysis. They possess a very strong Bronsted acidity and appropriate redox properties that make them excellent catalysts in substoichiometric quantities. This review will focus on describing new developments in the application of HPAs in the organic synthesis of heterocycles. Heterocycles that will be covered include coumarins, flavones, chromones, quinazolidones, dihydropyrimidinones, imidazoles, isoxazoles, pyrimidines, tetrazines, pyrazoles, dihydropyridines, and others.